Particle-level visualization of hydrodynamic and frictional couplings in dense suspensions of spherical colloids - Yanagishima, T; Liu, Y; Tanaka, H; Dullens, RPA (American Physical Society, 2021)
The rotational Brownian motion of colloidal spheres in dense suspensions reflects local hydrodynamics and {contact forces}, both key to non-linear rheological phenomena such as shear-thickening and jamming, and transport in crowded environments, including intracellular migration and blood flow. To fully elucidate the role of rotational dynamics experimentally, it is crucial to measure the translational and rotational motion of spheres simultaneously. Here, we directly access hydrodynamic and frictional coupling in colloidal suspensions up to arbitrarily high volume fractions using compositionally uniform colloidal spheres with an off-center, fully embedded core. We reveal interparticle hydrodynamic rotation-rotation coupling in charged colloidal crystals. We also find that higher local crystallinity in denser hard-sphere crystals enhances rotational diffusivity and that nearly arrested particles exhibit a stick-slip rotational motion due to frictional coupling. Our findings shed new light on the largely-unexplored local rotational dynamics of spherical particles in dense particulate materials.